ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA - Tati Herlina; Dina Dia (Jurnal Manajemen Bisnis Unbara, 2020)
Data analysis techniques used is descriptive qualitative. Based on the results of the study showed that the performance of the company PT. Semen Baturaja before and after the IPO at the current ratio of the company has fluctuated, this change has a very good company performance when before IPO this was because after the IPO the company was able to achieve a ratio of 385% while after the IPO the company's current ratio reached only 8.26%. DER and DAR of fluctuated but when compared before and after the IPO the value is more spread before the IPO. company net profit margin has a very high value but if compared to before and after the IPO, the company has a higher net profit margin value after the IPO in 2012 38%. Gross Profit Margin, Operating Profit Margin, ROE and ROA are the ratio shows the same thing, namely a ratio that has a higher ratio before the IPO and after the IPO switches to a lower ratio. The Simple Paired test shows that the value of t arithmetic <t table (0.860 <2.06390) and P value (0.398> 0.05) then H0 is accepted meaning that there is no difference between the financial performance of the company before and after the initial public offering (IPO)